Procedure for preparation, certification, and storage of a seed lot of the Mycobacterium bovis BCG-I (Russia) vaccine strain - D. T. Levi; R. I. Ludannyy; Yu. I. Obukhov; A. A. Savina; A. A. Alesina; N. V. Aleksandrova (Биопрепараты: Профилактика, диагностика, лечение)
To date, the Bacillus Calmette–Guérin (BCG) vaccine has been the only medicinal product for active mass childhood immunisation against tuberculosis in the Russian Federation. Industrial-scale batches of the BCG vaccine are manufactured using a seed-lot system, which provides for producing the vaccine for civil circulation from a single batch of seed material, a lyophilisate of Mycobacterium bovis BCG. National and international documents touch upon the evaluation of BCG vaccine seed material in terms of its quality attributes in small separate sections containing brief descriptions and/or lists of attributes and control methods. It is relevant to bring together the information on receipt, certification, and storage of the inoculum (the seed lot) for production of the Russian BCG vaccine. The aim of the study was a comparative assessment of the main characteristics of and control methods for the inoculum of the Russian vaccine strain, M. bovis BCG-I, set out in the national and international requirements for BCG vaccines. The article summarises literature data on the history of BCG substrains and the variability of their characteristics and presents a brief account of the origin of the Russian BCG-I substrain. It considers the control methods specified in the national and international requirements for the inoculum for the BCG vaccine. The study demonstrated the practical possibility of identifying BCG down to the substrain level with subsequent determination of genetic properties that characterise genomic stability of the substrain. The article presents the results of the comparative analysis of data on stability of lyophilisates of M. bovis BCG-I seed lots (Russia). Particular attention is paid to biological methods for controlling the seed lot (determination of residual virulence, including BCG survival) and the immunobiological method for controlling BCG for the absence of the genes responsible for virulence antigen expression (animal skin tests with Diaskintest®). The authors concluded that the control of stability of genetic and biological properties throughout the entire period of seed lot production and storage makes it possible to obtain BCG vaccines that meet all the regulatory requirements.